1980
DOI: 10.2331/suisan.46.583
|View full text |Cite
|
Sign up to set email alerts
|

Comparative biochemical studies on plasma cholesterol. II. Relationship between plasma esterified cholesterol and lecithin: Cholesterol acyltransferase activity.

Abstract: In five animals, blue crab, crayfish, carp, rat and man; their plasma lecithin: cholesterol acyltransferase (LCAT) activities were determined from the aspect of comparative biochemistry. The activities of mammalian blood plasma are much higher than those of carp blood and crustacean haemolymph plasma. Moreover, it was found that there is an apparent linear relationship between the LCAT activities and the ratios of cholesterol ester to total cholesterol. But the ratios of trigly cerides to total lipids do not c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1982
1982
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…It has been reported that, when clawed lobsters, Homarus sp., were fed a phosphatidylcholine deficient diet, their cholesterol transport was negatively affected (D'Abramo, Bordner, & Conklin, ), and a similar situation was also reported for the Kuruma shrimp, M. japonicus (Teshima & Kanazawa, ). Mankura, Dalimunthe, and Kayama () compared the level of cholesterol esterification in crustaceans, fish, rats, and human beings and suggested that crustaceans had the lowest lecithin: cholesterol acyltransferase activity, which is responsible for cellular cholesterol metabolism, particularly cholesterol contained in plasma lipoproteins. In a previous study with P. pelagicus juveniles of a size similar to those used here, dietary phospholipid (PL) supplementation was reported to markedly improved their growth, and optimal growth was achieved when the crabs were fed diets containing a PL level of >79 g/kg PL (Noordin et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that, when clawed lobsters, Homarus sp., were fed a phosphatidylcholine deficient diet, their cholesterol transport was negatively affected (D'Abramo, Bordner, & Conklin, ), and a similar situation was also reported for the Kuruma shrimp, M. japonicus (Teshima & Kanazawa, ). Mankura, Dalimunthe, and Kayama () compared the level of cholesterol esterification in crustaceans, fish, rats, and human beings and suggested that crustaceans had the lowest lecithin: cholesterol acyltransferase activity, which is responsible for cellular cholesterol metabolism, particularly cholesterol contained in plasma lipoproteins. In a previous study with P. pelagicus juveniles of a size similar to those used here, dietary phospholipid (PL) supplementation was reported to markedly improved their growth, and optimal growth was achieved when the crabs were fed diets containing a PL level of >79 g/kg PL (Noordin et al, ).…”
Section: Discussionmentioning
confidence: 99%